Impact of Leadership on Corporate Social Responsibility in Mexico - Rodriguez, Gianna (International Journal of Leadership and Governance, 2023)
Purpose: The study sought to analyze the impact of leadership on corporate social responsibility in Mexico. Materials and Methods: The study adopted a desktop methodology. Desk research refers to secondary data or that which can be collected without fieldwork. Desk research is basically involved in collecting data from existing resources hence it is often considered a low cost technique as compared to field research, as the main cost is involved in executive's time, telephone charges and directories. Thus, the study relied on already published studies, reports and statistics. This secondary data was easily accessed through the online journals and library. Findings: The results show that corporate governance and corporate social responsibility have become increasingly important in Mexico. The country works to improve its economic and social environment. Leadership is one of the most important aspects of corporate governance and corporate social responsibility. Leadership has the power to shape a company's culture and drive its strategic direction which can have a direct effect on corporate governance and corporate social responsibility. Unique Contribution to Theory, Practices and Policies: The Stakeholder theory and Political theory may be used to anchor future studies in the corporate governance sector. The study results will also benefit other stakeholders such as the policy makers as well as researchers and scholars from different parts of the world. The top management of corporate companies in the country will also use the study findings to improve the leadership and ensure high and stable performance in all their activities and programs. The study recommends that the adoption of effective corporate social responsibility policies in the corporate sector will help to improve efficiency in their major operations and activities.